Using The Non-Linear Autoregressive Distributed Lag -Regression Model To Study The Effect Of Inflation On Stock Returns "Econometric Study On Insurance Companies Listed On The Damascus Stock Exchange For The Period (2012-2019)" - بيطار , شادي; علي, بتول (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study deals with analyzing the effect of asymmetric inflation on the returns of the Syrian Insurance Sector Stock Index, using the Non-linear Autoregressive Distributed lag-Regression Model for the period 2012-2019 on a monthly basis, to describe the phenomenon in question and to study the nature of the impact of both positive and negative changes in the inflation of the stock returns of insurance companies listed on the Damascus Stock Exchange, according to the model used by (Tayraki,Erdogan) in 2018, on the returns of the stock market in the G7 countries. The study concluded that there was an adverse effect of the inflation rate on stock returns, and the two effects of both positive and negative inflation in the returns of insurance companies' shares were similar.